Survival benefit of preoperative hepatic arterial infusion of oxaliplatin, fluorouracil, and leucovorin followed by hepatectomy for hepatocellular carcinoma - Hu, Zili; Yang, Zhenyun; Pan, Yangxun; Fu, Yizhen; Wang, Jiongliang; Zhou, Zhongguo; Chen, Minshan; Hu, Dandan; Zhang, Yaojun (Frontiers in Pharmacology, 2023)
Background: Hepatic arterial infusion chemotherapy (HAIC) with cisplatin, fluorouracil, and leucovorin (FOLFOX) demonstrated promising efficacy against advanced hepatocellular carcinoma (HCC) as an alleviative treatment. We aimed to explore the survival benefit of preoperative FOLFOX-HAIC and establish a predictive nomogram.Methods: This study retrospectively reviewed data from 1251 HCC patients who underwent liver resection. 1027 patients received liver resection alone (LR group), and 224 patients were treated with FOLFOX-HAIC followed by liver resection (HLR group). Propensity score matching (PSM) was conducted between the two groups. The nomogram was established based on the findings of the multivariable Cox regression analysis.Results: After PSM according to initial tumor characteristics, the 1-, 2-, and 3-year OS rates were 85.4, 72.0, and 67.2% in the LR group and 95.2, 84.7, and 75.9% in the HLR group, respectively (p = 0.014). After PSM according to preoperative tumor characteristics, the 1-, 2-, and 3-year OS rates were 87.9, 76.6, and 72.3% in the LR group and 95.4, 84.4, and 75.1% in the HLR group, respectively (p = 0.24). Harrell's 3 C-indexes of the nomogram for OS prediction in patients with preoperative FOLFOX-HAIC were 0.82 (95% CI 0.78-0.86) in the training cohort and 0.87 (95% CI 0.83-0.93) in the validation cohort and the nomogram performed well-fitted calibration curves. Conclusions: Preoperative FOLFOX-HAIC is associated with a longer survival outcome for HCC patients. The novel nomogram efficiently predicted the OS of patients who underwent preoperative FOLFOX-HAIC.